2003
DOI: 10.1002/bit.10629
|View full text |Cite
|
Sign up to set email alerts
|

Potential of cell retention techniques for large‐scale high‐density perfusion culture of suspended mammalian cells

Abstract: This review focuses on cultivation of mammalian cells in a suspended perfusion mode. The major technological limitation in the scaling-up of these systems is the need for robust retention devices to enable perfusion of medium as needed. For this, cell retention techniques available to date are presented, namely, cross-flow filters, hollow fibers, controlled-shear filters, vortex-flow filters, spin-filters, gravity settlers, centrifuges, acoustic settlers, and hydrocyclones. These retention techniques are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 76 publications
3
150
1
3
Order By: Relevance
“…Previous studies have shown that some cell lines are susceptible to hydrodynamic stress, presenting a significant decrease in cell viability when subject to stress levels above a threshold limit (Born et al 1992). However, due to the low viability drops observed in this work, the viability of CHO cells separated by hydrocyclones was kept above 92%, which is higher than the cell viability obtained for most cell retention devices reported by Voisard et al (2003). In this review article, a compilation of 21 works using different cell retention devices showed that in only two cases cell viability was kept at values higher than the minimum viability (92%) obtained in the present work.…”
Section: Mid-term Effects Of Hydrocycloning On Cell Viability and Apocontrasting
confidence: 77%
See 2 more Smart Citations
“…Previous studies have shown that some cell lines are susceptible to hydrodynamic stress, presenting a significant decrease in cell viability when subject to stress levels above a threshold limit (Born et al 1992). However, due to the low viability drops observed in this work, the viability of CHO cells separated by hydrocyclones was kept above 92%, which is higher than the cell viability obtained for most cell retention devices reported by Voisard et al (2003). In this review article, a compilation of 21 works using different cell retention devices showed that in only two cases cell viability was kept at values higher than the minimum viability (92%) obtained in the present work.…”
Section: Mid-term Effects Of Hydrocycloning On Cell Viability and Apocontrasting
confidence: 77%
“…In CHO-cell perfusion cultures with spin-filters, the efficiencies attained were in the range of 75-95% (Iding et al 2000), as compared to a minimum efficiency of 97.9% found for hydrocyclones in the present work. Furthermore, unlike hydrocyclones, fouling and clogging of spin-filter meshes is considered a major problem, which may cause premature interruption of the culture process (Esclade et al 1991;Deo et al 1996;Voisard et al 2003). Furthermore, when compared to other hydrocyclone geometries, the efficiencies found in the present work are higher than the best efficiency (81%) obtained for HeLa cells by Lübberstedt et al (2000b).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Different cell-retention systems are available for mammalian-cell culture and have been extensively discussed recently (Castilho and Medronho, 2002;Voisard et al, 2003;Woodside et al, 1998). Cell-retention systems available for perfusion systems at relatively large-scale (100-1,000 L/d) are spinfilters (Deo et al, 1996;Yabannavar et al, 1994), hollow fibers/alternating tangential-flow filters (Voisard et al, 2003), centrifuges (Johnson et al, 1996;Takamatsu et al, 1996), settlers (Arai et al, 1993), and acoustic cell separators (Gorenflo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-retention systems available for perfusion systems at relatively large-scale (100-1,000 L/d) are spinfilters (Deo et al, 1996;Yabannavar et al, 1994), hollow fibers/alternating tangential-flow filters (Voisard et al, 2003), centrifuges (Johnson et al, 1996;Takamatsu et al, 1996), settlers (Arai et al, 1993), and acoustic cell separators (Gorenflo et al, 2002). Acoustic separators have no physical barrier and no moving mechanical parts and are, therefore, less prone to fouling and mechanical failure.…”
Section: Introductionmentioning
confidence: 99%